Communication as social theory : the social side of knowledge management - Johannessen, Jon-Arild (Emerald Publishing Limited, 2021)
Communication as Social Theory: The Social Side of Knowledge Management develops a social theory at micro level, with communication as the essential social mechanism within the theory. Leadership expert Johannessen examines how we can advance communication as social theory. The communicative process has been framed as a sequence: select-create-detect. The 'select' element occurs when a positive choice to communicate something is made, thereby deselecting something else. In this book 44 case letters have been developed. These case letters are designed to deepen, underline and augment the 44 conceptual and empirical propositions that have been established. The core message is to promote change in social systems by focusing on changing micro-behaviours. In complex adaptable systems, the individual actors adapt their behaviour to each other on the basis of the local minimal rules. This means that one cannot take individual behaviour for granted, but one must instead investigate individual behaviour within specific contexts. For students of Management Studies and professionals in Leadership this work is a must for expanding their understanding.
Includes index.
Keywords: Personnel management.; Knowledge management -- Social aspects.; Communication in management.; Business & Economics -- Human Resources & Personnel Management.; Management & management techniques.; elektronické knihy; electronic books